Student Awareness and Perception of Food Chemical Safety: Identifying Risks and Knowledge Gaps - Manaog, Marta Milagros M.; Maroma, Dolly P.; Maroma, Allen N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Chemical in food have become a growing concern, especially among youths exposed to processed and artificial food products. Understanding students' awareness and perception of chemical safety in food is crucial for effective risk communication, policy development, and promoting informed consumer choices. Therefore, this descriptive study was conducted. It aimed to analyze the extent to which students understand the safety of chemicals in food, their perceived risks, and how external influences shape their food consumption decisions. One hundred fifty (150) Senior High School students from two strands participated in this study and were selected using stratified random sampling. A survey questionnaire was used to examine variables related to awareness, perceptions, external influences, knowledge of regulations, and decision-making concerning food chemicals. Descriptive statistics (frequency counts, percentages, and mean scores) are reported for each item. Inferential tests (chi-square, t-test, and ANOVA) were used where relevant to determine relationships and/or differences among subgroups (e.g., HE A, HE B, HUMMS A, and HUMMS B). The study revealed that no significant relationship exists between awareness of food chemicals and actual food consumption decisions. Furthermore, no significant differences in awareness scores were observed across academic strands, nor were significant differences in decision-making found between male and female students. Researchers conclude that schools should expand access to nutritious meal options within cafeterias, ensuring that students have viable alternatives to chemically processed snacks and beverages.